2020
DOI: 10.3389/fcimb.2020.570658
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Approach—A New Strategy to Treat Parkinson’s Disease

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder characterized by neuronal loss and dysfunction of dopaminergic neurons located in the substantia nigra, which contain a variety of misfolded a-synuclein (a-syn). Medications that increase or substitute for dopamine can be used for the treatment of PD. Recently, numerous studies have shown gut microbiota plays a crucial role in regulating and maintaining multiple aspects of host physiology including host metabolism and neurodevelopment. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 203 publications
(243 reference statements)
0
22
0
Order By: Relevance
“…Other studies have shown that certain bacteria belonging to Bacteroidetes ( Porphyromonas gingivalis ) was detected in brain and may be involved in neurodegenerative disease, particularly for Alzheimer disease [ 54 , 61 ]. However, for Parkinson disease, metabolites of the imbalanced gut microbiome, in particular Gram-negative pathogens, are the trigger for the loss of dopaminergic neurons and mitochondria dysfunction [ 62 , 63 ].…”
Section: Diseases That May Occur As a Results Of Microbiome Alterationmentioning
confidence: 99%
“…Other studies have shown that certain bacteria belonging to Bacteroidetes ( Porphyromonas gingivalis ) was detected in brain and may be involved in neurodegenerative disease, particularly for Alzheimer disease [ 54 , 61 ]. However, for Parkinson disease, metabolites of the imbalanced gut microbiome, in particular Gram-negative pathogens, are the trigger for the loss of dopaminergic neurons and mitochondria dysfunction [ 62 , 63 ].…”
Section: Diseases That May Occur As a Results Of Microbiome Alterationmentioning
confidence: 99%
“…Patients with Parkinson’s disease have obvious gut microbiota dysbiosis, which leads to an increase in the production of pro-inflammatory cytokines and a decrease in anti-inflammatory bacteria. Thus, gut microbiota dysbiosis is potentially related to Parkinson’s disease state and progression ( Liu et al, 2020 ). Alzheimer’s disease causes gut microbiota imbalance, facilitating the infiltration of peripheral immune cells into the brain parenchyma and enhanced microglial activation, contributing to cognitive decline and amyloid-β burden in a mouse model of Alzheimer’s disease ( Kim et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been used in the treatment of gastrointestinal infections or other diseases, and has been approved by the World Health Organization and the USA Federal Drug Administration (FDA) for clinical treatment ( Carlucci et al., 2016 ). FMT includes screening, homogenization, filtration, and reuse of fecal samples for specific microbiota, followed by colon administration or oral administration in the form of oral tube or capsule containing lyophilized substances ( Liu et al., 2020 ). Currently, it is believed that direct administration of FMT by colonoscopy is the most effective approach, but attention should be paid to the risk of bleeding.…”
Section: Microbial Therapymentioning
confidence: 99%